Construction of an integrative pre-hospital emergency care course in a certain Traditional Chinese Medicine university (高等中医药院校中西医结合院前急救公共选修课的构建) - LIN Keke (林可可); WANG Huifeng (王惠峰); YANG Lili (杨丽丽); YAN Lijiao (晏利姣); WANG Juan (王娟) (中西医结合护理)
Objective To construct an integrative pre-hospital emergency care course in a certain Traditional Chinese Medicine university. Methods The expert consultation form was designed based on training materials of pre-hospital emergency care and literature review. Suggestions and comments were collected from twenty clinicians and faculty members with expertise in pre-hospital emergency care training. Results Forty-two items were selected as the teaching content by the two-round consultation. The credit hours, teaching methods and the selection criteria for clinical teachers were also finalized. Conclusion The integrative pre-hospital emergency care course constructed by the two-round expert consultation is scientifically sound. It can serve as a reference for other universities when constructing a similar course. (目的 构建高等中医药院校中西医结合院前急救公共选修课。方法 基于院前急救培训素材及文献回顾设计专家咨询表, 方便选取从事急救临床与护理的医务人员及高等院校从事急救相关教学的教师20人进行专家咨询。结果 通过两轮咨询, 最终确定课程内容包括基础生命支持、常见急症及中医急救三个方面共42个条目。同时确定了课时数、理论课与操作课的教学方法、临床师资的遴选标准等课程设置相关内容。结论 本研究通过专家咨询法构建的院前急救中西医结合公共选修课程具有科学性, 可为兄弟院校开设类似课程提供参考。)